2016
DOI: 10.1109/jtehm.2016.2599185
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Difference in Center-of-Pressure Positions Between Experts and Novices During Asymmetric Lifting

Abstract: Although numerous studies have analyzed the relationship between manual material handling (MMH) and the forces acting on the lumbar spine, the difference in the MMH between experts and novices through the analysis of measured data has not been well studied. The purpose of this paper was to analyze the difference in the MMH positions between ten skilled experts working at a freight transport company (Group 1) and five unskilled novices without any experience (Group 2) during asymmetric lifting. All the human su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 48 publications
0
12
0
1
Order By: Relevance
“…Jeong et al [15] used a WBB to analyze the difference in manual material handling between experts and rookies at a logistics workplace. Huurnik et al [16], Clark et al [17], and Park and Lee [18] demonstrated the validity and test-retest reliability of the WBB by measuring the CoP position and comparing the data with that from an identical study using a laboratory-grade force plate.…”
Section: Cross-check Of Experiments Resultsmentioning
confidence: 99%
“…Jeong et al [15] used a WBB to analyze the difference in manual material handling between experts and rookies at a logistics workplace. Huurnik et al [16], Clark et al [17], and Park and Lee [18] demonstrated the validity and test-retest reliability of the WBB by measuring the CoP position and comparing the data with that from an identical study using a laboratory-grade force plate.…”
Section: Cross-check Of Experiments Resultsmentioning
confidence: 99%
“…As mentioned in the Introduction, the accuracy of the data obtained in the systems examined in other studies was based on either movement similarity or similarity of pose. However, in our study [84][85][86], since differences can occur even at different weights in isotonic movements made with weights in the gym environment, the accuracy of the decisions made by the system was compared with the decisions of the certified coach. For this purpose, the participants were asked to perform DSP and LR exercises for one set of 10 repetitions (50%-90% load, one set of 10 reps), as in [87].…”
Section: Decisions Of Rule-based Expert Systemmentioning
confidence: 99%
“…By disregarding , the number of human model parameters to be identified can be considerably reduced [ 3 ]. are the distribution gains for vGRF which can be calculated from the body configuration [ 28 , 29 ] (N.B. is a necessary condition).…”
Section: Overloading Joint Torquementioning
confidence: 99%